1997
DOI: 10.1136/bmj.314.7080.547
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime socioeconomic position and mortality: prospective observational study

Abstract: Objective: To investigate the effect of socioeconomic group (with reference to age and sex) on the rate of, course of, and survival after coronary events. Design: Community coronary event register from 1985 to 1991. Setting: City of Glasgow north of the River Clyde, population 196 000. Subjects: 3991 men and 1551 women aged 25-64 years on the Glasgow MONICA coronary event register with definite or fatal possible or unclassifiable events according to the criteria of the World Health Organisation's MONICA projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
278
3
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(299 citation statements)
references
References 33 publications
(34 reference statements)
15
278
3
3
Order By: Relevance
“…Evidence suggests that the cumulative life experience influences health trajectories in a way that no static timepoint can capture. [26][27][28][29] Despite this evidence, it has been difficult to find a way to better account for the collective effect of lifetime SES. Indeed, evidence has shown that the effects of socioeconomic disparities on health may have the most impact earlier in life, perhaps due to mortality selection.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the cumulative life experience influences health trajectories in a way that no static timepoint can capture. [26][27][28][29] Despite this evidence, it has been difficult to find a way to better account for the collective effect of lifetime SES. Indeed, evidence has shown that the effects of socioeconomic disparities on health may have the most impact earlier in life, perhaps due to mortality selection.…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy diet, lack of exercise and drug use, particularly tobacco use, has only become strongly associated with social disadvantage relatively recently (Tate, 1999). This may explain why, in some studies, consideration of established physiological and behavioural risk factors seems to account for only a relatively small proportion of relative inequality in health between social groups (Davey Smith, Hart, Blane, Gillis & Hawthorne, 1997) (Marmot, Bosma, Hemingway, Brunner & Stansfeld, 1997). Similarly, access to health technology appears to be socially patterned and as technology becomes more effective this patterning is likely to contribute to health inequalities (Watt, 2002).…”
Section: Possible Pathways Between Social Position and Healthmentioning
confidence: 99%
“…Whether participants regularly drove a car was measured based on a single question on this. An area-based measure of deprivation was derived from the postcode of participant's normal place of residence according to the system of Carstairs and Morris (Carstairs & Morris, 1991) (Davey Smith, Hart, Blane, Gillis & Hawthorne, 1997). Scores were categorised as deprived (scores 6-7), middle (scores 4-5) and affluent (scores 1-3).…”
Section: Social Position Measuresmentioning
confidence: 99%
“…The first team is responsible for the Midspan prospective cohort studies conducted in the west of Scotland on adult men and women in the 1970s. These studies have generated novel findings on the use of social, lifestyle and health factors to predict mortality [4][5][6][7][8] , hospital admissions 9; 10 , and specific disease outcomes such as cardiorespiratory illness 11 , stroke 12 and cancer 13 . The participants have been followed up for mortality and cancer since inception, and have recently been linked with the Scottish Morbidity Records (SMR) system, enabling data on physical and mental illness to be investigated.…”
Section: Introductionmentioning
confidence: 99%